Comparison of the Effect of Ranibizumab and Aflibercept on Changes in Macular Choroidal Thickness in Patients Treated for Diabetic Macular Edema - Valérie Sarda; Pauline Eymard; Linda Hrarat; Franck Fajnkuchen; Audrey Giocanti-Aurégan (Journal of Ophthalmology)
Purpose. The aim of this study was to assess the effect of intravitreal injections (IVI) of ranibizumab and aflibercept on the choroidal thickness (CT) in patients with treatment-naive diabetic macular edema (DME) before and after monthly IVI. Patients and Methods. Prospective monocenter study. Inclusion criteria were treatment-naive DME eyes without concomitant panretinal photocoagulation, associated with a decrease in best-corrected visual acuity ≤75 letters on the Early Treatment Diabetic Retinopathy Study (ETDRS) scale. DME was defined by a central retinal thickness ≥300 μm on swept-source OCT (Triton DRI OCT, Topcon Corporation, Itabashi, Japan). Patients received 5 IVI of ranibizumab or aflibercept. The primary endpoint was the change in the central subfield CT (CSCT) between inclusion (M0) and 1 month after the fifth IVI (M5). The secondary endpoint was the CT changes between M0 and M5 in other locations of the macular ETDRS grid. Results. Twenty-four eyes of 24 patients with a mean age of 61.1 years were included. Eleven and 13 patients were, respectively, treated with ranibizumab and aflibercept, and 86.4% had type 2 diabetes. The overall CSCT decreased significantly by −12 μm between M0 and M5 (231.7 μm at M0 and 219.7 μm at M5) (p=0.03). It decreased by −15.2 μm (p=0.02) in the aflibercept group (206.9 μm at M0 and 191.7 μm at M5) and by −7.3 μm (p=0.4) in the ranibizumab group (267.5 μm at M0 and 260.2 μm at M5). The CSCT decreased by −4.9 μm in noninjected contralateral eyes (242.3 μm at M0 and 237.4 μm at M5). CT changes between M0 and M5 in the superior, temporal, inferior, and nasal macular inner ring were significant in the aflibercept group but not in the ranibizumab and control groups. Conclusion. In DME patients, the CSCT decreases after 5 IVI of anti-VEGF, especially after aflibercept treatment.